2022
DOI: 10.1002/htj.22624
|View full text |Cite
|
Sign up to set email alerts
|

The flow of MHD Maxwell liquid over an extending surface with variable free stream temperature

Abstract: The aim of this article is to investigate the steady twodimensional flow of a magnetohydrodynamics Maxwell liquid over a stretched exterior having prescribed exterior hotness in the presence of changeable free stream temperature. Here the Maxwell liquid replica reflects non-Newtonian liquid behavior. By means of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Here, as limiting instances, we verify the accuracy of our numerical results and compare them with the published articles. Thus, we compare the study's results with those reported in references [42], [44], and [50][51][52][53][54]. As Table 2, Table 3, and Table 4 demonstrate, our results are found to be in strong agreement.…”
Section: Numerical Scheme Testingsupporting
confidence: 73%
See 1 more Smart Citation
“…Here, as limiting instances, we verify the accuracy of our numerical results and compare them with the published articles. Thus, we compare the study's results with those reported in references [42], [44], and [50][51][52][53][54]. As Table 2, Table 3, and Table 4 demonstrate, our results are found to be in strong agreement.…”
Section: Numerical Scheme Testingsupporting
confidence: 73%
“…Comparison of the SLM finding of βˆ’π‘“ β€²β€² (0) with those found in[50][51][52][53] for various values of 𝛽 1 when 𝛽 2 = 𝑓𝑀 = 𝑀 = 𝐺𝑐 = πΊπ‘Ÿ = 0.…”
mentioning
confidence: 95%